EFECTIVENESS ELECTRONIC NEWSPAPER OF ADVERTISING TAMAN MARGASATWA KASANG KULIM KABUPATEN KAMPAR PROVINSI RIAU - Ayu Septiana; Andi Moh Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of this research is to know effectiveness electronic newspaper of advertising messages which had performed by Taman Margasatwa Kasang Kulim’s Management. The sampels on this research are 100 people, who are taken by using slovin. Based on the objectives to be achieved, this research used descriptive quantitative technique with percentage method as the result statements of visitor’s respond. The results of this research are based on the visitors’s respond, the success rate effectiveness electronic of advertising messages Taman Margasatwa Kasang Kulim was reached at 72.1%. The figur show that the advertisement has been applied by Taman Margasatwa Kasang Kulim is quite effective Keywords : Effectiveness, Advertising Messages, Electronic Newspaper,   Attraction